Organizational Management in the VUCA Hydrogen Era: Towards a Hybrid Model of Adaptive Theories - Sánchez-Rojas, Pablo Mauricio; Peñuela-Lizcano, José David; Zea-Sandoval, Miguel Ángel; Galleguillos-Madrid, Felipe M.; Eguigure-Torres, Yenny; Bedoya-Ávalos, José Rolando; Bonaza-Alzuria, Ignacio; Medina-Almendra, María Elena; Casanueva-Yáñez, Galvarino (Journal of Cultural Analysis and Social Change, 2026)
In a world defined by volatility, uncertainty, complexity, and ambiguity (VUCA), energy organizations must rapidly adapt to the transition towards clean and sustainable sources, such as green hydrogen and other renewable energies. This manuscript explores the transformation of organizational management within this context, emphasizing the importance of integrating classical theories with emerging paradigms to address the challenges of the contemporary energy sector. The analysis reveals that, while traditional management theories provide a solid framework for understanding organizational dynamics, their capacity to respond to the speed of technological change and the fluctuations of the energy market is limited. In this regard, organizations must adopt a more flexible and adaptive approach that fosters innovation and collaboration among diverse actors such as academia, industry, and government. A hybrid model of adaptive management is proposed, combining the stability of classical organizational structures with the agility and collective intelligence demanded by VUCA environments in hydrogen era. This approach seeks not only to optimize operational efficiency but also to promote a culture of continuous learning and experimentation, essential for facing the uncertainty inherent in the adoption of new energy technologies. The manuscript concludes that the integration of classical management theories with digital and agile approaches enables a more comprehensive understanding of organizational phenomena in the energy sector. This theoretical synthesis is crucial for developing effective strategies that not only address the specific challenges of hydrogen and other renewable energies but also facilitate the transition towards a more sustainable and resilient global energy future.